Impactos das políticas públicas educacionais mineiras, no período de 2003 a 2014, sobre a saúde do professor da rede estadual de Uberaba - REIS, Juliana Christina de Souza (2016)
This thesis goal was to investigate the impacts of the deployment of the subsidy law/2011 about the teaching illness during the “Choque de Gestão” government policy context, in the period between 2003 and 2014, in Uberaba´s public education system. For this, the submitted methodology was based on the Politics Cycle that analysed the influence contexto and the practical contexto leading from the following research tools: Semi-structured interview, papers and SEPLAG data. Having all the research tools two categories have been related: “Education context in Minas Gerais and educational public policies „‟ and “ Teaching illness and the impacts caused by the subsidy law/2011 in the Choque de Gestão policy contexto”. Upon a strict analysis the conclusion was that the subsidy law contributed for the teaching illness, once it favoured the job conditions failing and the teaching impoverishment, as in “Choque de Gestão” context the aim was the tax adjustment, educational area investments were withdrawn, just as well IPSEMG health insurance plan, leaving the teachers in bad financial conditions and inappropriate medical assistance. As well as, professionalization and continuous training could not mitigate the impacts from the stressing elements around the teachers.